Climate change and sustainable development : new challenges for poverty reduction - Salih, Mohamed Abdel Rahim M. (Edward Elgar Pub., 2009)
This unique book provides cutting-edge knowledge and analyses of the consequences that climate change will have for sustainable development and poverty reduction within the context of global development. Exploring alternative resource management approaches including federal resource management governance, ecosystem services, digital dematerialization, ecological cities, biofuels versus food, and children and climate change, this innovative volume provides fresh insights on the human condition with regards to the current debates on climate change. The distinguished contributors examine climate change induced processes that present profound challenges to sustainable development and poverty reduction at the local, national and global levels. This groundbreaking study will be a welcome addition for graduate and post-graduate students in development and environmental studies. It will also have great appeal to scientists, policy-makers and researchers in these fields.